The lost history of Christianity: the thousand-year golden age of the church in the Middle East, Africa, and Asia- and how it died - Jenkins, Philip (HarperOne, 2009)
A note on names and -isms -- The end of global Christianity -- Churches of the East -- Another world -- The great tribulation -- The last Christians -- Ghosts of a faith -- How faiths die -- The mystery of survival -- Endings and beginnings